2018
DOI: 10.5530/fra.2018.2.12
|View full text |Cite
|
Sign up to set email alerts
|

GC- MS, FTIR, UV Analysis and in vitro Antioxidant Activity of a Nigeria Poly Herbal Mixture: Pax Herbal Bitters

Abstract: Objective:The use of herbal products by the majority is primarily based on the belief that herbal drugs are safe, without any side effects, accessible and available at minimal cost. However, there is need for quality assurance of the botanicals in these products in order to meet the demands of product quality and efficacy. In this study, we aimed at identifying the chemical compositions of Pax herbal bitters towards a better understanding of its pharmacological claims. Methods: Pax herbal bitters purchased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hence its elevation can precipitate a negative cardiovascular event (Ho et al, 2013). MDA's reaction with lysine residues generates lysinelysine cross-links which have been identified in apolipoprotein B (apoB) fractions of oxidized low density lipoprotein (OxLDL), and have been postulated to impair the interaction between OxLDL and macrophages and thereby to promote atherosclerosis (Ho et al, 2013) and indirectly causing hypertension which is a major hallmark of syndrome (Jegatheesan, and De Bandt, 2017;Elufioye and Mada, 2018). Antioxidants are major key players in mitigating the adverse effect of oxidative stress by continuous eradication of excess free radicals, and its depletion equals an increased oxidative stress induced cellular and systemic destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence its elevation can precipitate a negative cardiovascular event (Ho et al, 2013). MDA's reaction with lysine residues generates lysinelysine cross-links which have been identified in apolipoprotein B (apoB) fractions of oxidized low density lipoprotein (OxLDL), and have been postulated to impair the interaction between OxLDL and macrophages and thereby to promote atherosclerosis (Ho et al, 2013) and indirectly causing hypertension which is a major hallmark of syndrome (Jegatheesan, and De Bandt, 2017;Elufioye and Mada, 2018). Antioxidants are major key players in mitigating the adverse effect of oxidative stress by continuous eradication of excess free radicals, and its depletion equals an increased oxidative stress induced cellular and systemic destruction.…”
Section: Discussionmentioning
confidence: 99%
“…iii. Shogaol (15.16%, known to be anti-tussive nd antioxidant (Elufioye and Mada, 2018;Anionye and Onyeneke, 2020). The results of this study showed that the detrimental impact of a high fructose diet causing inflammation and oxidative stress, as evidenced by the elevation of Hs-CRP and MDA levels and the reduction in TAC, were successfully ameliorating by Paxherbal bitters.…”
Section: Discussionmentioning
confidence: 99%